EdTech Evidence From Covid-19 Response: A thematic review of primary research from Bangladesh, Ghana, Kenya, Pakistan and Sierra Leone - Nicolai, Susan; Jefferies, Kate; Stepanek Lockhart, Ashley (EdTech Hub, 2023)
To better understand the use of EdTech interventions as part of response to the Covid-19 pandemic, EdTech Hub commissioned ten small-scale research studies in five low- and middle-income countries: Bangladesh, Ghana, Kenya, Pakistan, and Sierra Leone. This paper includes insight into research methodologies across these studies, with particularly interesting findings on how EdTech effectiveness is being measured. A semi-structured thematic analysis further provides insights in relation to four main user groups of learners, girls, teachers, and parents and caregivers and points to a series of cross-cutting factors that are important for EdTech interventions in low-resource settings. An overarching takeaway centres on the fact that having technology in place is a small part of EdTech effectiveness, with wider teaching and learning ecosystems accompanying EdTech deserving more attention. Overall, the studies reveal a symbiotic relationship between people and technology, reinforcing that EdTech works best when users are involved across design, iteration, awareness building, and engagement. Keywords: EdTech, Covid-19, digital, education, learning, remote An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7074857 ZenodoArchiveConcept: 7074856 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.6326179 10.5281/zenodo.7074857 10.53832/edtechhub.0114 2405685:K5BJUBRE 2405685:REW8F5TJ 2405685:U6G7C62D
Keywords: _r:AddedByZotZen

Messaging Apps, SMS, and Social Media: A Rapid Evidence Review - Jordan, Katy; Mitchell, Joel (EdTech Hub, 2020)
This Rapid Evidence Review (RER) provides an overview of existing research on the use of mobile phone-based messaging (including SMS, and messaging through apps such as WhatsApp) to support education in low- and middle-income countries (LMICs). This topic was chosen as the focus for a RER in response to the Covid-19 pandemic and school closures, as this form of technology has been adopted as part of some countries’ methods of providing continuing education during closures and disruption. As such, the overall purpose of this document is to summarise the existing research literature around messaging, so that the existing evidence can be used to inform ongoing responses to the pandemic. The findings are intended to be of use to educational decision makers, including donors and those in government and NGOs, to inform responses to the current pandemic.
ZenodoArchiveID: 4556938 PreviousDOI: 10.5281/zenodo.4058181 PreviousDOI: 10.5281/zenodo.4477015 KerkoCite.ItemAlsoKnownAs: 10.5281/ZENODO.4058181 10.5281/ZENODO.4556938 10.5281/zenodo.4477015 10.5281/zenodo.4556938 2339240:8QFLYEYK 2339240:ATYZFQ8R 2339240:CUBEJEWS 2339240:LCAUL9ZC 2339240:NISQD6JT 2339240:T2Z992XW 2339240:XMQV9Y56 2339240:YGQCMSDP 2405685:2GE8ESCR 2405685:4G8DT7ZB 2405685:4JM6QWPH 2405685:5NMCR3LL 2405685:EQVI8NMV 2405685:IU849P3E 2405685:MMTHETFR 2405685:PY3CXCH9 2405685:QSD5LYSF 2405685:XHBPFYVC 2405685:Z7P9NRWJ
Keywords: Covid-19; LMICs; SMS; Social media; TPD; WhatsApp; _DOILIVE; _EdTechHub_Output; _GS:indexed; _MELA_seen; ___working_potential_duplicate; _cover:v3; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH; educational technology; mobile learning; refugee education; teacher professional development; text message; ⛔ No DOI found

Factors Related to Teacher Absenteeism in Sierra Leone: Literature review - Vijil, Alejandra; McBurnie, Chris; Bellinger, Amy; Godwin, Katie; Haßler, Björn (EdTech Hub, 2023)
This report is one of several on the research project on the Impact of GIS-Supported Teacher Allocation in Sierra Leone (Hub-Led Research Programme 3). The education workforce is the most important school-level determinant of student learning. In Sierra Leone, the pupil-to-qualified-teacher ratio rises from 44:1 for schools in urban centres to 76:1 for schools in rural areas. Meanwhile, an average of a quarter of the workforce is absent from school on any given day. This informal literature review provides a summary of the most recent literature on teacher absenteeism, covering a wide range of low- and middle-income countries, including Sierra Leone, where the larger study is being undertaken. For the purposes of this review, we have focused on lessons learnt from sub-Saharan African studies that share similar education contexts and challenges as Sierra Leone. Based on the review, we hypothesise that distance from a teacher’s home to their school and their ability to choose which school they would like to work in impact teacher motivation, school attendance, and time on task. Efficient teacher allocation could improve each of these outcome estimates. An output of the EdTech Hub, https://edtechhub.org
oldDOI: 10.5281/zenodo.6498098 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.6498098 10.5281/zenodo.7716253 10.53832/edtechhub.0082 10.53832/edtechhub.0170 2339240:7MIS2I79 2405685:MS3CKE8G 2405685:T3F6DCHP 2405685:UJWVTSCK
Keywords: _r:AddedByZotZen

Covid-19 and EdTech in Africa: A Country-Level Review Based on eLearning Africa Data - Damani, Kalifa (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 4703718 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4703718 2405685:CDC2W7Q6 2405685:HVQVC8TU
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _r:AddedByZotZen; _zenodo:submitted; _zenodoETH

Sierra Leone Digital Learning Landscape Analysis: Developing the National Digital Learning Strategy - Waziri, Nafisa; Mufti, Abdal; Ramesh Vasudevan, Sharanya; Beoku-Betts, Iman; Oyedele, Oluwatomisin (EdTech Hub, 2025)
In 2024, the World Bank submitted a request to EdTech Hub's Helpdesk to support the Government of Sierra Leone in developing a National Digital Learning Strategy. The Hub initiated the process with the creation of this digital learning landscape analysis. The report identifies achievements and progress to date, as well as key challenges and priority areas going forward. It is based on primary and secondary data collection methods, including key informant interviews, focus group discussions, and a comprehensive desk review. Other relevant sources to gain insight into existing EdTech initiatives, interventions, and challenges within the country were also reviewed. Keywords: EdTech; National Digital Learning Strategy; landscape analysis; Ministry of Basic and Senior Secondary Education; Teaching Service Commission. An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 13256782 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1053 ZenodoArchiveConcept: 13256781
Keywords: _r:AddedByMyEducationEvidence

Teacher Continuous Professional Development in Tanzania: Lessons Learnt - Chachage, Kristeen; Thakrar, Jay (EdTech Hub, 2023)
This report shares the experience and learning from the activities carried out as part of the Government of Tanzania's efforts to operationalise its National Framework for Teacher Continuous Professional Development (TCPD), which shifts TCPD from discreet workshops to cost-effective, ongoing, school-based professional development. It is among the first of its kind at a national level, particularly in low- and middle-income country contexts. Through a collaborative and responsive approach of adaptive technical assistance and innovation, the EdTech Hub team supported Government of Tanzania partners in developing and implementing a technology-enhanced, school-based, national TCPD system. This report begins with an overview of the activities implemented and then consolidates reflection through nine lessons learnt that could help inform current and future thinking on the design, delivery, and funding of TCPD programming in Tanzania. The TCPD reflected in this report is specific to Tanzania's teaching and learning environment. While we recognise that environments can vary widely, even between countries with similar goals and objectives, the report also seeks to contribute to any current and future analyses that collate features of effective TCPD from around the world. Keywords: teacher professional development; teacher training; technology; learning management system; communities of learning; teacher needs assessment; An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7677950 ZenodoArchiveConcept: 7677949 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7677950 10.53832/edtechhub.0157 2339240:RBNTBT7Z 2405685:9WBV8KPN 2405685:EGL4QHDZ
Keywords: _r:AddedByZotZen

Designing Teacher Learning Circles for Improved Foundational Numeracy Outcomes: Findings from the National Numeracy Programme in Malawi - Correa de Oliveira, André; Plaut, Daniel; Kanyoza, Charity; Boilo, Violet; Chidothi, Emmanuel; Kadzamira, Esme; Mpoola, Dorothy; McBurnie, Chris; Phiri, Magret; Haßler, Björn (EdTech Hub, 2024)
The Malawi National Numeracy Programme (NNP) was designed in 2020 in partnership with the Malawi Ministry of Education and Cambridge Education (Mott McDonald), funded by the UK Foreign, Commonwealth and Development Office (FCDO). Building on findings from a prior qualitative review of the NNP's programme components, EdTech Hub proposed a new phase of design-based implementation research (DBIR) to be undertaken in Term 2 of the 2022–2023 school year to refine the school-based teacher continuous professional development (TCPD) model of the NNP. As part of the research, EdTech Hub developed a new TLC guide to be tested in schools. Through observations, focus group discussions, and interviews, the Hub gathered teacher feedback and used it to co-design and iterate on this guide alongside teachers. This report summarises the principal findings from the study. It also outlines the research background, methodology, findings, and recommendations for the programme moving forward. Keywords: teacher continuous professional development, teacher learning circles, National Numeracy Programme (NNP), Malawi, design-based implementation research An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7568301 ZenodoArchiveConcept: 7568300 KerkoCite.ItemAlsoKnownAs: 2129771:VEW2PXA5 10.5281/zenodo.7568301 10.53832/edtechhub.0177 2405685:2AN8XVIA
Keywords: _r:AddedByZotZen